A quasi-transient coupling approach to the modeling of conjugate heat transfer in the autoclave. (December 2021) - Zhu, Junhong; Frerich, Tim; Dimassi, Adli; Droste, David; Herrmann, Axel S
Structural aerospace composite parts are generally cured in an autoclave. To achieve a homogeneous curing, computational fluid dynamics simulations have been increasingly used in thermal optimization. However, a transient computational fluid dynamics simulation of autoclave processing is resource intensive. This article outlines the concept of a quasi-transient coupling strategy to deal with the conjugate heat transfer problem inside an autoclave. In this approach, a computational fluid dynamics model is coupled with a finite element method (FEM) model through incorporating an empirical-based analytic equation, which describes the dependence of the heat transfer coefficient on pressure and temperature, into the computational fluid dynamics computations. This approach bridges the temporal disparities between the fluid and the solid, thus minimizing the global computing time. To validate this method, two simulation cases have been studied. In both cases, two different coupling computations are compared, namely a full-transient simulation as the reference computation and the introduced quasi-transient simulation. First, the quasi-transient coupling approach is implemented by performing the transient heat transfer analysis on a flat plate. The results indicate that this approach can predict accurate transient temperature fields, and the computational effort is reduced by up to 87%. Subsequently, this method is used in a real autoclave and validated by known experimental data. The simulation results are in good agreement with the experimental results, with a mean temperature error lower than 1.9°C. This indicates the capability and efficiency of this approach in solving a conjugate heat transfer problem for autoclave processing.